![](https://tex.z-dn.net/?f=+)
please please give me answer
Attachments:
![](https://hi-static.z-dn.net/files/d5d/d5d514dc08aacd1d3e0d4c598622aed7.jpg)
Answers
Answered by
5
Step-by-step explanation:
here, put ax = tanΦ , Φ = tan^(-1)(ax)
we know, 1 + tan²Φ = sec²Φ
here we know ,
cos2Φ = 1 - 2sin²Φ
cos 2Φ -1 = -2sin²Φ
taking (-1) on both the sides
-cos 2Φ + 1 = 2sin²Φ
2sin²Φ = 1 - cos2Φ
1 - cosΦ = 2sin²(Φ/2)
And, Sin2Φ = 2sinΦ. cosΦ
therefor
sinΦ = 2 sin(Φ/2).cos (Φ/2)
here, ![theta = tan^{-1}(ax ) theta = tan^{-1}(ax )](https://tex.z-dn.net/?f=theta+%3D+tan%5E%7B-1%7D%28ax+%29)
Similar questions